Parents of babies who participated in an invasive clinical study report a positive experience: the Glucose in Well Babies (GLOW) study. Issue 1 (30th October 2019) - Cumberpatch, Alana R; Weston, Philip J; Harding, Jane E; Harris, Deborah L
Abstract : Objective: There is a paucity of data about normal blood metabolite concentrations in healthy babies, in part because of a reluctance to undertake non-therapeutic invasive testing in newborns. The Glucose in Well Babies study (GLOW) sought to describe blood glucose, lactate and beta-hydroxybutyrate concentrations in healthy term babies over the first 5 postnatal days. We also sought to understand both parents' experience of participation in this invasive non-therapeutic study. Design, setting, patients and interventions: Eligible babies were healthy, term, appropriately grown singletons born in a birthing centre, hospital or home within the greater Hamilton area and then discharged home. Babies had subcutaneous continuous glucose monitoring placed soon after birth, up to 14 heel-prick blood samples, twice-daily home visits and parents were asked to record all feeds. At study completion, both parents were asked to independently complete a questionnaire about their experience. Results: All eligible babies completed the study and every parent completed the questionnaire (65 fathers, 66 mothers). Parents reported they liked contributing to improving healthcare (126/131, 96%) and support from the GLOW team (119/131, 91%). Nearly all (127/131, 97%) would participate in GLOW again if they had another eligible baby, and all would recommend GLOW to family and friends. Two-thirds of parents (87/131, 66%) reported that participation had made them more likely to contribute to clinical research in the future. Conclusions: Non-therapeutic studies involving invasive procedures in healthy term babies are feasible, and parents were positive about their experience.